Imunitas Selular – Netrofil - Huldani Huldani (Berkala Kedokteran, 2014)
Abstract: Neutrophils play a role in nonspecific cellular immune system which can be found in circulation. Neutrophils are white blood cells (leukocytes) are characterized histologically by its ability to stained by the dye neutral and functional with its role in mediating the immune response against infectious microorganisms. . Neutrophil granules are usually pink or purple - blue with dye. Neutrophil Approximately 50 to 80 percent of all white blood cells in the human body. Neutrophils are quite uniform in size with a diameter between 12 and 15 micrometers. The core consists of 2-5 lobes joined together by the hairlike filaments. Neutrophils move by amoeboid movement. In neutrophils migrate to the area of the body to infection or tissue injury. Tensile strength which determines the direction in which neutrophils will move known as chemotaxis and is associated with substance released from the damaged tissue. Neutrophils are active phagocytes that engulf bacteria and other microorganisms and microscopic particles. The granules of neutrophils is a powerful enzyme that can digest various types of cellular material. During the inflammatory response, chemotactic factors of different origin and proinflammatory cytokine signals attracting neutrophils to the site of infection and / or injury. Injured area will issue a neutrophil chemo attractant attractive to the injured area, followed by the formation of reactive oxygen species (ROS) which is used as the body's defenses. Neutrophils also synthesize and secrete small amounts of several cytokines including IL-1, IL-6, IL-8, TNF-α, and GM-CSF. Keywords: Cellular Immunity - Neutrophils - Chemo attractant Abstrak: Netrofil  berperan dalam sistem imun nonspesifik selular yang dapat ditemukan dalam sirkulasi. Neutrofil adalah sel darah putih ( leukosit ) yang ditandai secara histologi oleh kemampuannya untuk ternoda oleh pewarna netral dan fungsional dengan perannya dalam mediasi respon imun terhadap mikroorganisme menular. . Granul neutrofil biasanya berwarna merah muda atau ungu - biru dengan zat pewarna . Netrofil Sekitar 50 sampai 80 persen dari semua sel darah putih dalam tubuh manusia. Neutrofil cukup seragam dalam ukuran dengan diameter antara 12 dan 15 mikrometer . Inti terdiri dari 2-5 lobus bergabung bersama oleh filamen mirip rambut . Neutrofil bergerak dengan gerakan amoeboid. Dalam tubuh neutrofil bermigrasi ke daerah infeksi atau cedera jaringan . Kekuatan tarik yang menentukan arah di mana neutrofil akan bergerak dikenal sebagai kemotaksis dan berhubungan dengan zat yang dilepaskan dari tempat kerusakan jaringan. Neutrofil adalah fagosit aktif yang dapat menelan bakteri dan mikroorganisme lain dan partikel mikroskopis . Granul neutrofil merupakan  enzim kuat yang mampu mencerna berbagai jenis bahan selular. Selama respon inflamasi, faktor chemotactic asal yang berbeda dan sinyal sitokin proinflamasi menarik neutrofil ke tempat infeksi dan / atau cedera. Daerah yang mengalami cedera akan mengeluarkan chemo attractant yang menarik neutrofil ke daerah cedera tersebut, diikuti pembentukan reactive oxygen species (ROS) yang digunakan sebagai pertahanan tubuh. Neutrofil juga mensintesis dan mensekresi sejumlah kecil beberapa sitokin termasuk IL-1, IL-6, IL-8, TNF-α, dan GM-CSF. Kata-kata Kunci : Imunitas Selular – Netrofil – Chemo attractant